Consequences of Hypervitaminosis D in NZW Rabbit Model: Vitamin D Toxicity - Ahmed, Mohamed; Prasad, Kailash; Shoker, Ahmed (Universitas Airlangga, 2025)
Background and Aim: This study examines the effect of hypervitaminosis D on serum lipids and on kidney functions in New Zealand White (NZW) rabbit. It aims to study whether renal insufficiency or failure, due to hypervitaminosis D, is calcium-related or not. As well, it also discusses a possible link between hypervitaminosis D and hypercholesterolemia. Methods: Four Groups of six animals each, were divided into: Group I, received regular diet, Group II received regular diet +10,000/day vitamin D2; Group III, received 0.25% cholesterol diet; as well as Groups IV received 0.25% cholesterol diet plus 10,000 IU. Blood samples were taken at the end of the study and examined for Total Cholesterol (TC), Triglycerides (TG), Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL), Blood Urea Nitrogen (BUN), Creatinine, Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Alkaline Phosphatase (ALP), Calcium and Phosphate. As well, 25- hydroxyvitamin D (25 (OH) D) was measured using tandem LC-MS/MS. Results: The initial (0 time) serum TC, TG, LDL, HDL, Creatinine, Calcium, Phosphate and 25 (OH) D levels were not significantly different among different groups including control. At 1- and 2-month time, values from serum TC, TG, LDL, HDL and TC/HDL-C ration of Groups III and IV were significantly different from controls (p<0.05). As well, values from serum 25 (OH) D of Group II and IV were significantly different from controls (p<0.05) at 1- and 2-month time. However, values from serum Creatinine and Calcium of Group II were significantly different from controls (p<0.05) at 1- and 2-month time. Conclusion: Hypervitaminosis D may aggravate hypercholesterolemia, and it also induces renal insufficiency and/ or failure through a calcium-dependent mechanism. – Highlights: 1. Excessive vitamin D supplementation, particularly when combined with a hypercholesterolemic diet, aggravated hyperlipidemia and elevated serum calcium levels in NZW rabbits. 2. Hypervitaminosis D was associated with increased serum creatinine and hypercalcemia, suggesting potential renal impairment secondary to excessive vitamin D intake